Evaluation of anti-hypertensive activity of ancient Unani cardiovascular drug "Saad Kufi" (Cyperus scariosus) in adrenaline-induced hypertensive rats - Sana Nafees; Syed Ziaur Rahman; Kunwar Mohammad Yousuf Amin (SpringerOpen, 2020)
Abstract Background Saad Kufi (Cyperus scariosus R.Br) is a hardy grass-like perennial plant that belongs to the family Cyperaceae. Ibn Sina (Avicenna), the most significant thinkers and writers of the Islamic Golden Age first time systematized the individual cardiac drugs in "Risala Advia Qalbia," which deals with 63 cardiac drugs which are claimed to be beneficial for heart ailments as well as for psychiatric ailments. He described Saad as a root of a plant that is nodular, long, and slender and resembles the wheat plant. The roots which used medicinally are thick, elongated, slender, and color black and has an aromatic smell with a pungent taste. An antihypertensive effect of 50% ethanolic extract of Saad Kufi (Cyperus scariosus R.Br) [EESK] was evaluated in adrenaline-induced hypertension in Wistar albino rats. The induction of systolic blood pressure (SBP) and the percentage of inhibition was measured in EESK (15 and 25 mg/100 g, orally) with standard as Metoprolol (0.5 mg/100 g) orally, using tail-cuff apparatus with AD instrument power lab to evaluate the antihypertensive effect. Results EESK significantly decreased the induction in SBP as compared to disease control rats (p < 0.05), and there is a significant increase in the percentage of inhibition in SBP in EESK and metoprolol-treated rats as compared to the disease control group (p < 0.05). Conclusion Result data suggest that EESK possess significant antihypertensive activity in adrenaline-induced hypertensive rats.